2016
DOI: 10.1016/j.celrep.2016.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-Wave Ripples Orchestrate the Induction of Synaptic Plasticity during Reactivation of Place Cell Firing Patterns in the Hippocampus

Abstract: SummaryPlace cell firing patterns reactivated during hippocampal sharp-wave ripples (SWRs) in rest or sleep are thought to induce synaptic plasticity and thereby promote the consolidation of recently encoded information. However, the capacity of reactivated spike trains to induce plasticity has not been directly tested. Here, we show that reactivated place cell firing patterns simultaneously recorded from CA3 and CA1 of rat dorsal hippocampus are able to induce long-term potentiation (LTP) at synapses between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 77 publications
4
124
0
Order By: Relevance
“…This idea is supported by studies interrupting SWRs during offline processing (sleep) that found impairments in the acquisition of hippocampus‐dependent spatial tasks (see also Ref. ) and activity in cortical and subcortical structures temporally aligned to the SWR . However, this view does not explain why SWRs are frequently observed during pauses in task performance and appear to signal trajectories leading to a goal location (prospective) rather than replaying the recently taken trajectory (retrospective) .…”
Section: Internally Generated Sequences In the Hippocampus And Their mentioning
confidence: 99%
“…This idea is supported by studies interrupting SWRs during offline processing (sleep) that found impairments in the acquisition of hippocampus‐dependent spatial tasks (see also Ref. ) and activity in cortical and subcortical structures temporally aligned to the SWR . However, this view does not explain why SWRs are frequently observed during pauses in task performance and appear to signal trajectories leading to a goal location (prospective) rather than replaying the recently taken trajectory (retrospective) .…”
Section: Internally Generated Sequences In the Hippocampus And Their mentioning
confidence: 99%
“…It is currently controversial whether hippocampal synapses are potentiated or exclusively depressed during SWRs (Bukalo, Campanac, Hoffman, & Fields, ; Buzsaki, ; Buzsaki, Haas, & Anderson, ; Colgin, Kubota, Jia, Rex, & Lynch, ; King, Henze, Leinekugel, & Buzsaki, ; Leonard, Mcnaughton, & Barnes, ; Norimoto et al, ; Sadowski, Jones, & Mellor, ; Tononi & Cirelli, ). Nevertheless, both synaptic potentiation and depression have been proposed as mechanisms for memory consolidation (Bukalo et al, ; Norimoto et al, ; Sadowski et al, ; Tononi & Cirelli, ). Those hippocampal synapses supporting frequently replayed rewarding sequences may be further strengthened and/or other synapses are weakened during SWRs, so that relative strengths of frequently replayed sequences are enhanced.…”
Section: Implementation Of the Simulation‐selection Modelmentioning
confidence: 99%
“…The related hypothesis is that repeated neuronal co-activation strengthens newly formed assemblies (Hebb, 1949). Offline reactivation is most prominent during sharp wave-ripple (SWR; 125–250 Hz) oscillatory events (Wilson and McNaughton, 1994, Buzsáki, 2015a) in which conditions indeed promote Hebbian synaptic plasticity (Sadowski et al., 2016). Consistent with a role for reactivation in memory consolidation, co-firing patterns associated with spatial novelty or rewarded learning are reactivated more strongly (O’Neill et al., 2008, Singer and Frank, 2009, McNamara et al., 2014), and electrical disruption of hippocampal SWRs during sleep impairs subsequent memory recall (Girardeau et al., 2009, Ego-Stengel and Wilson, 2010).…”
Section: Introductionmentioning
confidence: 99%